Selected farm-level crop protection practices in Europe and Argentina: Opportunities for moving toward sustainable use of pesticides - Mark, Jennifer (2024)
Extensive use of plant protection products (PPP) in the last decades contributes to negative impacts on eco systems, animals and humans. For the strategies of PPP reduction and replacement of hazardous pesticides, farm level data on agronomic management practices and crop protection applications are crucial. In this study, we strategically collected data for the 2021 season at the SPRINT project case study sites (CSS) in 10 European countries and Argentina, on perennial, arable and vegetable crops. Data collection included strategically selected farm and field data, pesticide records and farming practices. Results involved more than 1700 recorded PPP applications across various crops with more than 170 different active substances from PPP in organic, integrated pest management and conventional farming practices. We explored differences in application patterns (fungi cides, insecticides, herbicides and non-PPP, e.g. adjuvants, growth regulators, and fertilizers) between and within crops, countries and farming systems and calculated the costs of PPP use. The pesticide dosages applied during the crop season varied up to a factor of 20 around recommended doses. Regarding the costs of PPPs use perennial crops had the highest costs per ha crop production area. Finally, we analysed the active substances applied in different farming systems in terms of their hazard statements. Our results shed light on how PPPs are used across different crop and farming types and will help elucidate how pesticide application patterns can be changed in the future. Finally, we highlighted non-PPP use practices which help to reduce dependency on PPP use. This might be used to support decision-making and policies within agricultural advisory/support systems.